DISKRIMINASI KEBIJAKAN PEMERINTAH INDIA TERHADAP KAUM MUSLIM DALAM PERSPEKTIF HUKUM HAK ASASI MANUSIA INTERNASIONAL: DISCRIMINATION OF INDIAN GOVERNMENT POLICY AGAINST MUSLIMS IN THE PERSPECTIVE OF INTERNATIONAL HUMAN RIGHTS LAW - Notoprayitno, Maya Indrasti; Louisa, Monique; Salsabilah, Nahdia (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2024)
The increase in religious-based conflicts is the result of the use of religion by officials of the ruling Indian government who want to attract sympathy and support from the Indian population who are Hindu, which is the most widely followed belief in India. Since 2014, the government's policies have been perceived by the Indian and international community to marginalize Indian Muslims, particularly with the Citizenship Amendment Bill (CAA 2019). This paper discusses the racism that arises due to the differentiation in beliefs in Indian citizens. The research conducted in this paper is normative legal research using the library method. The results of the analysis are discussed with reference to the International Covenant on Civil and Political Rights. It can be concluded that the sectarian conflict in India due to the Citizenship Law is a form of discrimination that is contrary to Article 18 of the International Covenant on Civil and Political Rights, so there needs to be a further process in upholding religious rights in India.